A stakeholder-driven approach to designing a peer recovery coach role for implementation in community-oriented primary care teams in South Africa - Bronwyn Myers; Kristen S. Regenauer; Kim Johnson; Imani Brown; Alexandra L. Rose; Nonceba Ciya; Sibabalwe Ndamase; Yuche Jacobs; Morgan S. Anvari; Abigail Hines; Dwayne Dean; Rithika Baskar; et al. (Addiction Science & Clinical Practice)
Abstract Introduction In South Africa, community-oriented primary care teams work to re-engage out-of-care people with HIV (PWH) in treatment, many of whom have substance use (SU) concerns. SU stigma is high among these teams, limiting care engagement efforts. Integrating peer recovery coaches into community-oriented primary care teams could shift SU stigma and improve patients’ engagement in care. The peer role does not exist in SA and represents a workforce innovation. To enhance acceptability, feasibility, and appropriateness for the local context, we engaged multiple stakeholder groups to co-design a peer role for community-oriented primary care team integration. Methods We used a five-step human-centered design process: (i) semi-structured interviews with healthcare worker (n = 25) and patient (n = 15) stakeholders to identify priorities for the role; (ii) development of an initial role overview; (iii) six ideation workshops with healthcare worker (n = 12) and patient (n = 12) stakeholders to adapt this overview; (iv) refinement of the role prototype via four co-design workshops with healthcare worker (n = 7) and patient (n = 9) stakeholders; and (v) consultation with HIV and SU service leaders to assess the acceptability and feasibility of integrating this prototype into community-oriented primary care teams. Results Although all stakeholders viewed the peer role as acceptable, patients and healthcare worker identified different priorities. Patients prioritized the care experience through sharing of lived experience and confidential SU support. Healthcare worker prioritized clarification of the peer role, working conditions, and processes to limit any impact on the community-oriented primary care team. A personal history of SU, minimum 1 year in SU recovery, and strong community knowledge were considered role prerequisites by all stakeholders. Through the iterative process, stakeholders clarified their preferences for peer session structure, location, and content and expanded proposed components of peer training to include therapeutic and professional work practice competencies. Service leaders endorsed the prototype after the addition of peer integration training for community-oriented primary care teams and peer mentoring to address community and team dynamics. Conclusion Stakeholder engagement in an iterative design process has been integral to co-designing a peer role that multiple stakeholder groups consider acceptable and that community-oriented primary care teams are willing to implement. This offers a methodological framework for other teams designing SU workforce innovations.